Effects of Tb(NO3)3 salt on the structural characteristics, optical, and radiation shielding properties of (PVA-PVP- PEG) polymeric composite films - Mohammed, Mervat I.; Zahran, Heba Y.; Zyoud, Samer H.; Shahwan, Moyad; Aydin, Cihat; Yahia, Ibrahim S.; Abdelhameed, Doaa (Springer, 2025)
Herein, this study introduces a simple, effective, and potentially successful approach to the preparation of polymeric composite systems using a Polyvinyl alcohol (PVA)-Polyvinyl pyrrolidone (PVP)-Polyethylene glycol (PEG) (PVA-PVP-PEG), (8:1:1) as the host polymeric blend with the inclusion of Tb(NO3)(3)-salt filler. The diffraction of X-rays (XRD), infrared spectroscopic (FTIR), Ultraviolet-visible (UV-vis) spectroscopy, and Phy-X/PSD software were utilized to analyze the modified samples' structures, identify their optical and radiation shielding properties. The XRD patterns show the presence of Tb(NO3)(3) phases inside the composite matrix, where adding filler causes modifications in the polymeric network's structure for filled composite samples. FTIR analysis showed that the Tb(NO3)(3)-salt interacted with the blend's functional groups via H-bond formation. The UV-Vis spectra analysis showed all samples, especially those loaded with 8.0 wt.% Tb(NO3)(3)-salt has the highest values for absorbance, dielectric constant, refractive index, extinction coefficient, and optical and electrical conductivity. Tauc's formula, the ASF model, and epsilon(i)-h(v) plots were all applied to investigate optically the band gap in great detail. The values of E-d and E-o and n(o) have been investigated using a single oscillator model where their values were controlled by Tb(NO3)(3)- salt content. Using calculated gap energy, various approaches were applied to obtain the conceptual significance of the linear refractive index (n). The nonlinear optical parameters chi((1)), chi((3)), and n(2) increased noticeably as the Tb(NO3)(3)-salt percentage is increased to 8.0 wt%. The suggested largely doped Tb(NO3)(3)-salt composites show great promise as a CUT-OFF laser filters and attenuators in addition to being used in laser power-limiting technology. Based on our results, the sample was 8.0 wt.% Tb(NO3)(3)-salt has better gamma-ray shielding properties than the others because it has the largest Tb(NO3)3-salt concentration. The study opens a new route to fabricate Tb(NO3)(3)/(PVA-PVP-PEG) polymeric composites with superior optical properties.
Keywords: Tb(NO3)(3)-salt; XRD; Optical dispersion; Energy band gap; Refractive index; Optical limiting